Optimization of a Semiflexible Demand-Responsive Feeder System in Suburban Areas Using a Memetic Algorithm - Fabio Sartori Vieira; Kenneth Sorensen; Pieter Vansteenwegen (Journal of Advanced Transportation)
Traditional bus operations in suburban areas are inefficient due to their fixed routes and timetables. Since suburban operations deal with low demand spread in a large area, the service stays underused for most off-peak hours. In order to render the operation profitable and increase the number of passengers on each bus, operators reduce the frequency of the service, which results in an increase of passenger waiting time for the service. As a solution to this problem, this paper introduces a demand-responsive public bus system that aims to adjust routes and timetables of a semiflexible system to the demand for transportation. The operation still offers a reliable service like the traditional system but aims to reduce the passenger travel time. A memetic algorithm is developed to optimize this demand-responsive system. For a network with 25 bus stops served hourly by three lines and with an average demand of 20 requests per hour, the memetic algorithm is demonstrated to reduce the passenger waiting time with almost 50% in comparison with a traditional system operating in the same network with fixed routes and timetable.